Perseroan Perorangan Pasca Undang – Undang Cipta Kerja Perubahan Paradigma Perseroan Terbatas Sebagai Asosiasi Modal - Sholikhatus Hidayati; Nuril Mochammad Ichtisom; Sumriyah Sumriyah (International Forum of Researchers and Lecturers, 2023)
The study aimed to analyze the concept of a Limited Liability Company after the enactment of Law Number 11 of 2020 concerning Job Creation, especially concerning the concept of capital association paradigm. This normative legal research uses a statutory, conceptual and comparative approach. The results shows that after the enactment of the Job Creation Law, there is a new form of legal entity, namely an Private Company which is specifically for MSE actors with the aim of facilitating business development for MSE actors by being able to form a legal entity with only one person as the founder/shareholder. This has indicated a change in the paradigm of Limited Liability Companies as a capital association. It is in the form of expansion of the concept of a Limited Liability Company where the establishment of a Private Company for MSEs was founded by 1 (one) person. This is nothing new considering Article 7 paragraph 5 and paragraph (7) of the Company Law that a company can be established only by one shareholder as in the establishment of BUMN and BUMD which is also regulated in the BUMN Law and PP. 45 of 2005 which allows the shares of Persero to be wholly owned by the state.